Weight gain in twin gestations: Are the Institute of Medicine guidelines optimal for neonatal outcomes? - Lal, Ann K. (J Perinatol, 2015)
OBJECTIVE: To assess neonatal outcomes according to gestational weight gain (GWG) in twins STUDY DESIGN: This was a retrospective cohort study of twins delivered at ≥ 24 weeks. GWG was defined using the IOM guidelines as the referent. Birthweight and NICU admissions were compared with Chi-square and ANOVA tests, stratified by BMI. RESULTS: In all three BMI groups, mean birthweight of the larger and smaller twin increased as GWG increased, p<0.01. For the underweight/normal weight group, both twins < 2500 g, <1500 g and small for gestational age decreased significantly as GWG increased. Birthweight < 2500 g increased in all groups with GWG below the IOM guidelines, p < 0.01. In the multivariate analysis, both twins < 2500 g was significantly decreased with GWG above IOM guidelines. There was no difference in NICU admissions with GWG above the IOM guidelines. CONCLUSION: GWG above the IOM guidelines may improve twin birthweights, with the findings most significant in underweight/normal weight women.